Pretreatment And Enzymatic Saccharification Of Mango Peel For Sugar Production - Nur Aisyah Jusoh; Latiffah Karim; Siti Radhiah Omar; Asma’ Ali (Asian Scholars Network (ASNet), 2024)
Non-Indexed Publication